1997
DOI: 10.1007/s002130050303
|View full text |Cite
|
Sign up to set email alerts
|

Flumazenil blockade of anxiety following ethanol withdrawal in rats

Abstract: In previous research, the drug flumazenil has been categorized both as a pure benzodiazepine antagonist and as a benzodiazepine partial agonist. The following studies used an elevated plus maze to test whether flumazenil would exert any antianxiety action in rats. While chlordiazepoxide (3.0 mg/kg), ethanol (0.75 g/kg), and the atypical benzodiazepine zolpidem (1.0 mg/kg) all significantly increased time spent on the open arms and percent open arm entries, flumazenil (1-10 mg/kg) alone did not produce any anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 33 publications
14
71
5
Order By: Relevance
“…For example, withdrawal from alcohol liquid diet, chronic injections, vapor exposure, or consumption from a single drinking bottle increase anxiety-like behavior in mice that persists for up to 48 h after alcohol exposure (Costall et al, 1988;Joshi et al, 2005;Kliethermes et al, 2004;Prediger et al, 2006;Sparta et al, 2007). Similar results have been obtained in rat models showing increased anxiety-like behavior during acute and early withdrawal from an alcohol liquid diet (Baldwin et al, 1991;Moy et al, 1997;Pandey et al, 1999;Rassnick et al, 1993). In the present study, we observed increased anxiety-like behavior in non-dependent mice 1 day after voluntary alcohol drinking as measured by an open-field thigmotaxy assay.…”
Section: Discussionsupporting
confidence: 55%
“…For example, withdrawal from alcohol liquid diet, chronic injections, vapor exposure, or consumption from a single drinking bottle increase anxiety-like behavior in mice that persists for up to 48 h after alcohol exposure (Costall et al, 1988;Joshi et al, 2005;Kliethermes et al, 2004;Prediger et al, 2006;Sparta et al, 2007). Similar results have been obtained in rat models showing increased anxiety-like behavior during acute and early withdrawal from an alcohol liquid diet (Baldwin et al, 1991;Moy et al, 1997;Pandey et al, 1999;Rassnick et al, 1993). In the present study, we observed increased anxiety-like behavior in non-dependent mice 1 day after voluntary alcohol drinking as measured by an open-field thigmotaxy assay.…”
Section: Discussionsupporting
confidence: 55%
“…In general, behavioral assessments were conducted after 15 days of exposure to the ED, between 5 and 6 h after the removal of the ethanol. This time point was selected on the basis of previous observations of anxiety-like behavior in our laboratory (e.g., Knapp et al, 1998;Moy et al, 1997Moy et al, , 2000.…”
Section: Liquid Dietmentioning
confidence: 99%
“…After adaptation to the laboratory for 5 days, they were individually housed and placed on a nutritionally complete lactalbumin-dextrose diet for 3 days (Frye et al 1983;Moy et al 1997). The experimental rats were exposed to a diet containing ethanol (ED; 7%, w/v), while control rats remained on the control diet in which the dextrose replaced the ethanol isocalorically.…”
Section: Animalsmentioning
confidence: 99%